The Effect of Guided Inquiry Accompanied by Virtual Laboratory on Students' Physics Learning Outcomes and Motivation - Subiki, Subiki; Bahari, Fajar; Nuraini, Lailatul (STKIP Singkawang, 2024)
This research purpose was to examine the effect of applying the guided inquiry learning model accompanied by a virtual laboratory on the results and motivation of studying physics in high school students. The chosen physics material is static fluid. The type of research used is a true experiment with the Posttest Only Control Group design. The population of this study was students of class XI MIPA at one of the public high schools in Mojokerto Regency. The sample was selected by cluster random sampling technique and assigned to class XI MIPA 1 as the control class and class XI MIPA 4 as the experimental class. The treatment was carried out three times and the next meeting was used for the post-test and questionnaire filling. Data on learning outcomes were obtained from post-test scores which were analyzed using the independent sample t-test technique, while motivational data were obtained from filling out questionnaires which were analyzed using the independent sample t-test technique. Based on the results of the research, it can be concluded that there is an effect of applying the guided inquiry learning model accompanied by a virtual laboratory on the results and motivation of studying physics in high school students. The results of this research are expected to be useful for teachers who experience problems in learning physics, especially in terms of the need for practical implementation.